2016
DOI: 10.1002/cphc.201600952
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the O 2p Orbital and Redox Reaction in LiMn0.6Fe0.4PO4 Nanowires Studied by Soft X‐ray Absorption

Abstract: The changes in the electronic structure of LiMn Fe PO nanowires during discharge processes were investigated by using ex situ soft X-ray absorption spectroscopy. The Fe L-edge X-ray absorption spectrum attributes the potential plateau at 3.45 V versus Li/Li of the discharge curve to a reduction of Fe to Fe . The Mn L-edge X-ray absorption spectra exhibit the Mn multiplet structure throughout the discharge process, and the crystal-field splitting was slightly enhanced upon full discharge. The configuration-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…By analyzing the pre-edge peaks of O K-edge and combining them with configuration-interaction full-multiplet calculations and FTIR spectroscopy, it is found that the 4.0 V voltage plateau could be attributed to the electron gain/loss in O 2p orbital with a strong charge transfer effect. [102] It should be noted that the presence of deactivated particles and the potential interference they may cause in the analysis of element charge states and chemical environments can complicate the interpretation of experimental results. However, the information on electrochemical performance provided in the above literature is insufficient for quantitatively determining the contributions of the Fe 2+ /Fe 3+ and Mn 2+ /Mn 3+ reactions to the capacity.…”
Section: Interaction Of Mn 2+ ↔Mn 3+ and Fe 2+ ↔Fe 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the pre-edge peaks of O K-edge and combining them with configuration-interaction full-multiplet calculations and FTIR spectroscopy, it is found that the 4.0 V voltage plateau could be attributed to the electron gain/loss in O 2p orbital with a strong charge transfer effect. [102] It should be noted that the presence of deactivated particles and the potential interference they may cause in the analysis of element charge states and chemical environments can complicate the interpretation of experimental results. However, the information on electrochemical performance provided in the above literature is insufficient for quantitatively determining the contributions of the Fe 2+ /Fe 3+ and Mn 2+ /Mn 3+ reactions to the capacity.…”
Section: Interaction Of Mn 2+ ↔Mn 3+ and Fe 2+ ↔Fe 3+mentioning
confidence: 99%
“…For LiMn 0.6 Fe 0.4 PO 4 nanowire material, the involvement of oxygen in charge compensation has also been observed. [ 102 ] During lithiation, samples with different SOC were subjected to XAS measurement in total fluorescence yield (TFY) and TEY modes (with probing depths of TEY and TFY ≈<3 and <100 nm, respectively). The peak shapes obtained from both measurement modes are similar, indicating that the Fe 2+ /Fe 3+ redox reaction occurred uniformly in bulk, at the surface, and only at low voltage regions.…”
Section: The Electronic Structure Variation Of Lmfp During Charge/dis...mentioning
confidence: 99%
“…XAS is sensitive to the valence states, bond covalencies, and spin states of selected elements [19][20][21][22][23][24][25] . In particular, soft X-rays can be used to probe transition metal (TM) 3d states through the allowed 2p-to-3d dipole transition, which quantitatively elucidates the redox-reaction-induced changes in the valence states upon electrochemical cycling [26][27][28][29][30][31] . Furthermore, the O K-edge XAS spectra reveals the changes in the electronic states of both O and TM ions based on the hybridization between the TM 3d and O 2p orbitals 26,[32][33][34] .…”
Section: Openmentioning
confidence: 99%
“…In particular, soft X-rays can be used to probe transition metal (TM) 3d states through the allowed 2p-to-3d dipole transition, which quantitatively elucidates the redox-reaction-induced changes in the valence states upon electrochemical cycling [26][27][28][29][30][31] . Furthermore, the O K-edge XAS spectra reveals the changes in the electronic states of both O and TM ions based on the hybridization between the TM 3d and O 2p orbitals 26,[32][33][34] . Co L-edge and O K-edge XAS spectral analyses indicate that both the Co and O ions in the LiCoO 2 cathode particles participate in the redox process 35 , although the changes in the microscopic chemical-state distributions of each element remain unexplored.…”
Section: Openmentioning
confidence: 99%
“…The spectral features that originate from O 2p orbitals hybridized with surrounding elements are well known to reflect the electronic states around oxide ions. 41,[47][48][49] The NEXAFS O K-edge spectra of NaV(SO 4 ) 2 were likely constructed from the O 2p orbitals hybridized with V 3d (t 2g and/or e g ) and V 4sp, and S-O s-bond signals appeared at approximately 529.6, 531.6, 545, and 538 eV. 49 The peak at 529.6 eV corresponds to the unoccupied hybridized orbital of the O 2p orbital and V 3d (t 2g ) orbital, [49][50][51] and this peak partially reversibly changed during the desodiation/sodiation process (i.e., increasing in the intensity during desodiation and decreasing during sodiation).…”
Section: Papermentioning
confidence: 99%